Pengaruh Kata Cashback Terhadap Peningkatan Penjualan Menggunakan Data Mining - Pratama, Fidya Arie (Puslitbang Kopertip Indonesia, 2019)
Modern era has many advantages for us one of the advantages is selling and buying process as we known is online shopping. There is one word which is loved by seller and buyer is cashback recently. Cashback became a favorite thing in online shopping, every seller using cashback for developing their selling, and every buyer using cashback for getting many benefits. In this research researcher analyzed the using of cashback by beauty product company which is used cashback as their program in special program last year. The aim of research is describing the important of cashback word in selling and buying process. The researcher used language theory as communication by George Yule. The researcher also used Data Mining for analyzing the data and giving a provement about the influencing of cashback in selling and buying. The researcher used Algoritma K-Means as a method of research and used Rapid Minner application for analyzing te data. The result of this research showed the word of cashback increased double selling rate for beauty product company.